Recombinant Human Granulocyte-Macrophage Colony Stimulating Factor (sargramostim) as an Alternative Therapy for Fistulizing Crohn’s Disease - Magno, Priscilla; Jiménez, Carlos E.; Ortiz, Zhamarie; Torres, Esther A. (Puerto Rico Health Sciences Journal, 2010)
Background: Impaired neutrophil function has been proposed in the pathogenesis of Inflammatory Bowel Disease. Failure to control the response to bacteria and bacterial products triggers the inflammatory cascade. Genetic disorders of neutrophil dysfunction exhibit gastrointestinal manifestations similar to Crohn’s disease. Treatments that enhance neutrophil and macrophage function with colonystimulating factors have been successful in these conditions. Some studies using sargramostin in patients with Crohn’s disease have suggested a beneficial effect in disease activity, including fistulizing disease. The goal of the study was to evaluate the safety and efficacy of sargramostin in patients with fistulizing Crohn’s disease who had not responded to conventional therapy or had developed adverse reaction to infliximab requiring discontinuation of the drug. Methods: Patients with fistulizing Crohn’s disease who had failed conventional therapy were recruited. Sargramostin 6μg/kg subcutaneously daily for 8 weeks was prescribed. Follow-up included clinical evaluation, exam of the fistulas, laboratories, CDAI score, adverse events, compliance with therapy, quality of life assessment, and baseline and post-treatment abdomino-pelvic MRI. Results: Three patients were enrolled. There were 4 perianal, 7 enterocutaneous and multiple enteroenteric fistulas. Two completed 8 weeks of treatment and 1 was discontinued at week 5 for a hypersensitivity reaction. Sargramostin was ineffective in all three. Conclusions: The small number of patients and the severity of their disease do not allow any conclusions about the drug effectiveness. Placebo controlled studies, perhaps with less complicated patients, are needed to define a role, if any, of this therapy in fistulizing Crohn’s disease. [P R Health Sci J 2010;1:60-65]